Benthic macroinvertebrate response to estuarine emergent marsh restoration across a delta-wide environmental gradient - Rubin, Stephen P.; Davis, Melanie J.; Grossman, Eric E.; Woo, Isa; De La Cruz, Susan E. W.; Nakai, Glynnis; Takekawa, John Y. (Frontiers in Ecology and Evolution, 2024)
Benthic invertebrates play vital roles in estuarine ecosystems, but like other taxa they have been excluded from former marshlands by diking and land use conversion. Dike removal is one way of restoring marsh, but the response of benthic invertebrates has been little studied. Also understudied is variation in benthic invertebrate communities across entire deltas, particularly in the Pacific Northwest of North America where deltas receive high flows and sediment loads for their size. Our goals were to evaluate invertebrate response to large-scale dike removal on the Nisqually River Delta in Puget Sound, Washington, U.S.A., characterize delta-wide invertebrate community variation, and relate invertebrate response and spatial variation to environmental conditions. We sampled invertebrates annually from one year before to three years after dike removal in restoring marsh, previously restored marsh, undisturbed reference marsh, and adjacent tidal flats. Marine taxa immediately colonized the area recently restored to tidal inundation and population size grew exponentially thereafter for several of them. Community composition and diversity recovered completely, and density and biomass were approaching recovery three years later. Invertebrate communities converged between restoring and pre-existing marsh (previously restored and reference), suggesting an influence of reestablished connectivity. Just offshore from the dike line, invertebrates declined one year after dike removal but then rebounded indicating resilience to shortterm disturbance. Dike removal effects were not detected farther offshore. Near the offshore edge of the delta, invertebrate biomass and body size were greater than elsewhere and a diverse assemblage of crustaceans, polychaetes, and bivalves was present. Farther inshore, tidal flats were dominated by a few species of small-bodied polychaetes and had higher density but lower biomass and diversity. Facultative detritivores, which can also filter feed, were the dominant feeding guild everywhere on the tidal flats. Density, biomass, diversity, and community composition on the marsh were more similar to the inner than outer tidal flats. Environmental variables most associated with invertebrate community variation were elevation, salinity, and sediment grain size and organic content. Our results are relevant to assessing performance and setting expectations for future restorations and have broad implications for the role of benthic invertebrates in estuarine ecosystems.